Clinicoepidemiological Profile of Short Stature at A Tertiary Care Centre in Bangladesh - Biswas, Rabi; Farzana, Nahid; Rahman, Sultana Nadira (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Short stature (SS) is a common pediatric problem, which can cause psychosocial disturbances both in parents and children. The goal of the evaluation of a child with SS is to identify the subset of children with pathologic causes so that appropriate timely intervention can be made. Objective: The aim of the study was to study the clinical, epidemiological, and etiological profile of SS at a tertiary hospital of Bangladesh. Methods: This was a cross-sectional study and was conducted in the department of pediatric endocrinology, over a period of 1 year (January 2021-December 2021). A total of 100 children aged 3-14 years, with height <-2SD below the mean height for age and sex were studied. Clinical history, examination, and laboratory evaluations were done to assess the cause of SS and the data were analyzed using appropriate statistical methods. Results: About 55% were female and 45% were male. The causes of SS were found to be familial SS (36%), constitutional growth delay of growth and puberty (12%), hypothyroidism (11%), growth hormone deficiency (8%), malnutrition (10%), chronic diseases (9%), genetic syndromes and skeletal problem (8%). Conclusion: The majority of short stature in children had normal variation of growth. Along with endocrine causes, chronic systemic illnesses and malnutrition still form a major bulk in the etiological profile of SS in Bangladesh. DS (Child) H J 2022; 38(2): 79-83